Brain-specific genes contribute to chronic but not to acute back pain. (9th September 2022) - Bortsov, Andrey V.; Parisien, Marc; Khoury, Samar; Martinsen, Amy E.; Lie, Marie Udnesseter; Heuch, Ingrid; Hveem, Kristian; Zwart, John-Anker; Winsvold, Bendik S.; Diatchenko, Luda
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Introduction: Back pain is the leading cause of disability worldwide. Although most back pain cases are acute, 20% of acute pain patients experience chronic back pain symptoms. It is unclear whether acute pain and chronic pain have similar or distinct underlying genetic mechanisms. Objectives: To characterize the molecular and cellular pathways contributing to acute and chronic pain states. Methods: Cross-sectional observational genome-wide association study. Results: A total of 375, 158 individuals from the UK Biobank cohort were included in the discovery of genome-wide association study. Of those, 70, 633 (19%) and 32, 209 (9%) individuals met the definition of chronic and acute back pain, respectively. A total of 355 single nucleotide polymorphism grouped into 13 loci reached the genome-wide significance threshold (5x10 -8 ) for chronic back pain, but none for acute. Of these, 7 loci were replicated in the Nord-Trøndelag Health Study (HUNT) cohort (19, 760 chronic low back pain cases and 28, 674 pain-free controls). Single nucleotide polymorphism heritability was 4.6% (P=1.4x10 -78 ) for chronic back pain and 0.81% (P=1.4x10-8) for acute back pain. Similar differences in heritability estimates between acute and chronic back pain were found in the HUNT cohort: 3.4% (P=0.0011) and 0.6% (P=0.851), respectively. Pathway analyses, tissue-specific heritability enrichment analyses, and epigenetic characterization suggest a substantial genetic contribution to chronic but not acute back pain from the loci predominantly expressed in the central nervous system. Conclusion: Chronic back pain is substantially more heritable than acute back pain. This heritability is mostly attributed to genes expressed in the brain.